2020
DOI: 10.1103/physrevb.101.144417
|View full text |Cite
|
Sign up to set email alerts
|

Iron telluride ladder compounds: Predicting the structural and magnetic properties of BaFe2Te3

Abstract: Since the discovery of pressure-induced superconductivity in the two-leg ladder system BaFe2X3 (X=S, Se), with the 3d iron electronic density n = 6, the quasi-one-dimensional iron-based ladders have attracted considerable attention. Here, we use Density Functional Theory (DFT) to predict that the novel n = 6 iron ladder BaFe2Te3 could be stable with a similar crystal structure as BaFe2Se3. Our results also indicate that BaFe2Te3 will display the complex 2×2 Block-type magnetic order. Due to the magnetic strict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…The resulting reconstructed band structure shown in Fig. 3(b) is in good agreement with extant calculations for the nonmagnetically ordered state of BaFe 2 2Se 3 [35]. The choice of this energy range guarantees Fe localized, atomic-like Wannier functions, with the correct site symmetry.…”
Section: Theory and Resultssupporting
confidence: 77%
“…The resulting reconstructed band structure shown in Fig. 3(b) is in good agreement with extant calculations for the nonmagnetically ordered state of BaFe 2 2Se 3 [35]. The choice of this energy range guarantees Fe localized, atomic-like Wannier functions, with the correct site symmetry.…”
Section: Theory and Resultssupporting
confidence: 77%
“…We conclude reminding readers that the study of ladders has received renewed attention in the context of iron-based superconductors where it has been reported that the ladder materials BaFe 2 X 3 (X = S, Se) become superconducting at high pressure [38][39][40][41][42][43][44][45][46], similarly as the Cu-ladders do. Moreover, exotic spin states involving antiferromagnetically coupled ferromagnetic spin "blocks" have been studied experimentally and theoretically [47][48][49][50][51][52][53][54], and predictions for such unusual spins arrangement in diffraction neutron scattering were made and confirmed. This is a fertile area where inelastic neutron scattering can make an impact similar as in cuprates when single crystals become available.…”
Section: Discussionmentioning
confidence: 86%
“…For example, the full five-orbital Hubbard model was investigated via the mean-field Hartree-Fock analysis [33][34][35][36], revealing a complex filling-Hund/Hubbard interaction magnetic phase diagram with many competing phases. Many of such phases were also confirmed by density functional theory [34,[37][38][39][40][41][42]. Moreover, the electronic properties of the multiorbital Hubbard model were extensively investigated via the dynamical mean-field theory [43][44][45], especially the orbital-selective Mott phase (OSMP), namely the possibility of the localization of a fraction of the conduction electrons (on one or more orbitals) [46][47][48][49].…”
Section: Introductionmentioning
confidence: 94%